Nilai-Nilai Kasih Sayang dalam Novel Jilbab Traveler Love Sparks in Korea Karya Asma Nadia - Hakiki, Khoirunnisa Nurul; Israhayu, Eko Sri (CV. Eduartpia Publisher, 2024)
Every individual is created with all needs that must be realized, one of which is the need for affection. Representations of affection can be seen in novel literary works through figures created by the author so that readers can learn values ​​or lessons. This research aims to describe the value of affection and their relevance to the need for affection in Maslow's hierarchy of needs in the behavior of characters in the novel Jilbab Traveler Love Sparks in Korea by Asma Nadia. The author uses a qualitative descriptive type of research with the research object focused on the values ​​of compassion using a literary psychology approach. The data used is in the form of text, quotations or words related to the values ​​of love sourced from the novel Jilbab Traveler Love Sparks in Korea by Asma Nadia. The data was collected using reading and note-taking techniques. The validity of the data was carried out through a credibility test using triangulation techniques. The author searches for and groups data related to the value of affection through the data reduction stage, namely by summarizing the main things to get a clearer picture of the object, presenting the data by describing and classifying the data according to the main problem in the form of a description of the value of affection to facilitate the interpretation stage. , and the verification or conclusion drawing stage is carried out by comparing the conformity between the statements of the research object and the meaning contained in the research data so that results are obtained in the form of a description of the entire research content. The results of the research show that there are values ​​of love in the characters in the form of devotion, help, kinship, loyalty and caring related to fulfilling the need for love according to Maslow's hierarchy of needs.